A Tinjauan Pustaka: Diagnosis Dan Tatalaksana Katarak Kongenital - Adha Nurhaniefah, Azmi; Putri, Giska Tri (CV. Jasa Sukses Abadi, 2024)
Congenital cataract is a disorder of the loss of transparency of the lens, sometimes causing a change in its refractive index that occurs during the first year or childhood of life. Congenital cataract is a rare eye disease, with a variable prevalence of 0.6-9.3/10,000 live births. However, this disease remains one of the main causes of visual loss in children. This disease is considered a preventable cause of blindness. However, late diagnosis and treatment will also have an adverse impact and can cause severe permanent blindness. Congenital cataracts have a significant impact on affected patients due to the low age of the target population and the deprivation amblyopia that can occur as a complication of this disorder. The method used in compiling this literature review is through searching literature from various sources using online searches with Google Scholar, Pubmed, and NCBI instruments within the last 5 years and using the keywords congenital cataract, diagnosis, management, management, treatment data that have been collected were analyzed scientifically and systematically. The data analysis technique used is descriptive and argumentative. The results of this study indicate that the diagnosis of congenital cataracts can be made through anamnesis, physical examination, and supporting examinations. The main treatment with good visual results is through early intervention with surgical procedures. The surgical techniques used include anterior Capsulotomy, Lens Aspiration & Vitrectomy anterior/Lansectomy, and IOL Implantation.